A Theoretical Model for the Relationship between Perceptions, Metaperceptions, and Relational Outcomes - LeBlanc III, H. Paul (Advances in Social Sciences Research Journal, 2018)
Perception is based on sense experience (Hume, 1748). Whereas, metaperception is perceptions (or ideas) about perception. Relationships are comprised of individuals who develop perceptions of self, perceptions of the relational partner, and perceptions of the relational partners’ perception of self and partner (metaperceptions). This article defines perception and metaperception and describes the cognitive components which shape individual’s meaning of their experience, and reviews research on perception, metaperception, co-orientation and the impact of these cognitions on relationships and relational quality. This article further reviews more current research on couple construction based upon combinations of perceptions and metaperceptions, then provides a theoretical model for describing relational dynamics as a consequence of communication emanating out of the degree of agreement of perceptions and metaperceptions between relational partners. Finally, this article further provides a direction for future research on improvement of relational outcomes. It is hoped that this theoretical model may prove useful for scholars and practitioners.